KAJIAN EFISIENSI PEMASARAN JAMBU AIR KING ROSE APPLE - Muhammad Buhari Sibuea; Muhammad Thamrin; Juwita Tarigan (AGRIUM: Jurnal Ilmu Pertanian, 2013)
This aim of this study was to determine the efficiency of the marketing king rose apple guava water in the district and sub-district Namorambe STM Hilir Regency Deli Serdang. Sampling method using census method that takes all the existing population. Data analysis method used is descriptive analysis. The results showed that there are two marketing channels king rose apple guava water is the first line (which is commonly used by professional growers) and the second line (which is commonly used by conventional farmers) in which both have been efficient. Then based on the results of the descriptive analysis it is known that the first marketing channels (professional farmers) is more efficient than the two marketing channels (conventional farmers).Keyword : marketing, king rose apple guava water